(untitled) (KYAMC Journal, 2026)
Background: One of the most prevalent eye disorders that manifests as a mass lesion on the eyelids is a chalazion and every age group exhibits it. Retained secretion from the Zeis or meibomian glands causes chalazion and it is a non-inflammatory process. Objectives: The aim of this study was to find out the prevalence and associated factors of chalazion in Sirajganj District. Materials and Methods: This cross-sectional type of descriptive study was carried out among the patients attending in the outpatient Department of Ophthalmology, North Bengal Medical College, Sirajganj over a period of 12 months from January to December 2025. Approval from the Ethical Review Committee (ERC) was obtained prior to the commencement of the study. Purposive sampling technique was used and pre-designed, validated, structured questionnaire was used to gather data on prevalence and associated factors of chalazion. Results: Out of 90 patients, the mean age was 52.38±8.78 years with male to female ratio 1: 2.46. Chalazion was found in 12 (13.33%) of the patients. Five (41.67%) of the patients had had high blood lipid concentration followed by stress 5 (41.67%), eyelid trauma 4 (33.33%), poor lid hygiene 3 (25.00%), seborrhic dermatitis 3 (25.00%), trachoma 3 (25.00%), chronic blepharitis 2 (16.67%), rosacea 2 (16.67%), tuberculosis 2 (16.67%), immunodeficiency 1 (8.33%) and viral infection 1 (8.33%). There was no statistically significant difference between gender and the development of chalazion (p=0.32). Conclusion: The findings of this study might help the ophthalmologists in their day to day diagnosis and prevention of chalazion. KYAMC Journal Vol. 16, No. 03, October 2025: 142-145.